Assessing the effectiveness of intensive outpatient care for Christian missionaries and clergy. - Rosik, Christopher H.; Summerford, April; Tafoya, Jennifer (Mental Health, Religion & Culture, 2009)
In the limited number of studies published to date, intensive outpatient programmes (IOPs) have demonstrated treatment effectiveness and financial benefits over higher continuum of care interventions. In this study, we sought to extend this research using a sample of full-time Christian workers (missionaries and clergy) admitted to an IOP specifically designed for religious professionals. We employed the Outcome Questionnaire - 45 (Lambert et al., 2004) as the dependent variable in this longitudinal analysis. A one-way repeated-measures ANOVA was conducted for pre-arrival, pre-treatment, post-treatment, and three-month follow-up assessments with an N of 142. Results indicated an effect for time of assessment, suggesting a significant treatment response. Follow-up, planned contrasts supported the interpretation of the time of assessment effect as stemming from IOP treatment. Participants' response sets appeared to contribute to more favourable self-presentations at pre-arrival, pre-treatment, and, to a lesser extent, post-treatment assessments. Some implications of these findings are discussed.